Ease of Doing Business in the Middle East: A Study From Investors’ Perspective - Fernandez, Manuel; Joseph, Robinson; Fernandez, Vania Maria (International Journal of Economics and Financial Issues, 2025)
The study aims to identify the most favorable nation in the Middle East for starting a new business using data published by the World Bank on Ease of Doing Business. The study focuses on ten factors: Starting a business, dealing with construction permits, obtaining electricity, registering property, getting credit, protecting minority investors, paying taxes, trading across borders, enforcing contracts, and resolving insolvency. The study seeks to provide insights for policymakers and investors in determining the most suitable investment destination in the Middle East. The study finds that currently, the UAE offers the most investor-friendly environment for investment with the top rank in Starting a business, Dealing with construction permits, Getting electricity, and Enforcing contracts; second rank for Registering property and Protecting minority investors; and third rank for Getting credit; and fifth rank for Resolving insolvency. The study concludes that the UAE currently has the most investor-friendly environment in the Middle East.